2002
DOI: 10.1016/s0168-583x(02)01436-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of ion-sputtered surfaces

Abstract: We derive a stochastic nonlinear continuum theory to describe the morphological evolution of amorphous surfaces eroded by ion bombardment. Starting from Sigmund's theory of sputter erosion, we calculate the coefficients appearing in the continuum equation in terms of the physical parameters characterizing the sputtering process. We analyze the morphological features predicted by the continuum theory, comparing them with the experimentally reported morphologies. We show that for short time scales, where the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
532
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(558 citation statements)
references
References 108 publications
(250 reference statements)
22
532
3
1
Order By: Relevance
“…Displaced atoms that reach the surface with enough kinetic energy to leave are permanently sputtered away; all other displaced atoms come to rest within the solid or on the surface after phonon emission times of ~10 − 12 s. These processes contribute prompt erosive 14,15 and prompt redistributive 11,16,17 components of morphology evolution and are collectively denoted P [x].…”
mentioning
confidence: 99%
“…Displaced atoms that reach the surface with enough kinetic energy to leave are permanently sputtered away; all other displaced atoms come to rest within the solid or on the surface after phonon emission times of ~10 − 12 s. These processes contribute prompt erosive 14,15 and prompt redistributive 11,16,17 components of morphology evolution and are collectively denoted P [x].…”
mentioning
confidence: 99%
“…[4,[7][8][9][10][11]. Initiated by advances in the statistical mechanics of various non-equilibrium systems, it has been observed that the roughness of many natural surfaces follows rather simple scaling laws, which can be quantified using scaling exponents.…”
Section: Methodsmentioning
confidence: 99%
“…The model is completed by expressing the currents and current densities in terms of the surface geometry and the surfactant density. Expressions for the erosion currents in the absence of surfactants are available from the theory of Bradley and Harper [12] and its generalizations [13,14,15]. In addition, we take into account modifications of the sputtering yields so that the erosion currents of substrate and surfactant, J A and J B , respectively, are given by…”
Section: Continuum Theory and Monte Carlo Modelmentioning
confidence: 99%
“…J 0 denotes the flux of incident ions, Y A , Y B are the sputtering yields of the pure A and B system, respectively. We keep the first terms of the standard gradient expansion of the yield modification due to surface morphology [12,15],…”
Section: Continuum Theory and Monte Carlo Modelmentioning
confidence: 99%